Atypical nodular astrocytosis in simian immunodeficiency virus‐infected rhesus macaques (Macaca mulatta). Issue 6 (1st August 2014) - Petrosky, Keiko Y.; Knight, Heather L.; Westmoreland, Susan V.; Miller, Andrew D.
Abstract Background Simian immunodeficiency virus (SIV), a model for HIV pathogenesis, is associated with neuropathology. Methods Five SIV‐infected animals were selected following a database search of 1206 SIV‐infected animals for nodular or astrocytic lesions. Two of five had neurologic dysfunction, and 3 of 5 were incidental findings. Results Histologic examination revealed multifocal nodular foci in the gray and white matter formed by interlacing astrocytes with abundant cytoplasm and large, reactive nuclei. Nodules were often enmeshed with small capillaries. Immunohistochemistry revealed variable immunoreactivity for a panel of markers: GFAP (4/5), vimentin (5/5), Glut‐1 (1/5), CNPase (0/5), S100 (5/5), Iba1 (0/5), Ki67 (0/5), and p53 (4/4). In situ hybridization failed to detect any SIV RNA (0/5). Immunohistochemistry for simian virus 40, rhesus cytomegalovirus, and rhesus lymphocryptovirus failed to detect any antigen within the lesions. Conclusion The immunoreactivity of p53 in the lesions compared with adjacent tissue suggests a local derangement in astrocyte proliferation and function.